Exploring figurative language of daughtering and fathering in Albert Nyathi's poem my daughter. - Viriri, Advice (2016)
The increasing availability of children's literature reflect on trans-cultural characteristics of Zimbabwe's cultural and socio-political spheres. Recurrent key motifs and themes cover a broad spectrum of African literature ranging from the prominence of female authors, female protagonists, introduction of elements of oral narratives, innovative uses of folktales to address social ills, to contemporary topical issues whose shifting focus gravitate towards 'modernity'. Nyathi's book My Daughter (2012) is a manifestation of a literary tradition influenced by figures of speech whose eclectic systems of meaning exhibit in formulating what children's literature ought to be. This article shows how My Daughter is a girl -child protection guide for parents who are meant to develop public awareness campaign against all forms of abuse. It further explains how this over-protection of the girl- child should not be misconstrued as an underestimation of the power of women in reconfiguring their sexuality. The book sensitises readers to the "anecdote which warns covetous men against prostitution " (Chiwome 1996: 83) which tears the African social fabric apart.The poetic recital, besides advocating for more effective family and national protection policies to guard vulnerable children against 'animals' of prey, highlights the educative value on how to protect and empower girl-children.